2012
DOI: 10.1007/s11103-012-9877-2
|View full text |Cite
|
Sign up to set email alerts
|

Kiwifruit floral gene APETALA2 is alternatively spliced and accumulates in aberrant indeterminate flowers in the absence of miR172

Abstract: In Arabidopsis, the identity of perianth and reproductive organs are specified by antagonistic action of two floral homeotic genes, APETALA2 (AP2) and AGAMOUS (AG). AP2 is also negatively regulated by an evolutionary conserved interaction with a microRNA, miR172, and has additional roles in general plant development. A kiwifruit gene with high levels of homology to AP2 and AP2-like genes from other plant species was identified. The transcript was abundant in the kiwifruit flower, particularly petal, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 61 publications
4
33
0
Order By: Relevance
“…Relatively high degrees of homology were also indicated between this cDNA and the AP2-like sequences from Arabidopsis. Additionally, we showed strong complementarity between CeAP2-like mRNA and miR172, as well as localization of the complementary nucleotides similar to that in the cDNAs of other homologous genes identified in different plant species (Nilsson et al, 2007;Varkonyi-Gasic et al, 2012). These results indicated the potential regulation of AP2 by miR172 in the orchid.…”
Section: Disscussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Relatively high degrees of homology were also indicated between this cDNA and the AP2-like sequences from Arabidopsis. Additionally, we showed strong complementarity between CeAP2-like mRNA and miR172, as well as localization of the complementary nucleotides similar to that in the cDNAs of other homologous genes identified in different plant species (Nilsson et al, 2007;Varkonyi-Gasic et al, 2012). These results indicated the potential regulation of AP2 by miR172 in the orchid.…”
Section: Disscussionsupporting
confidence: 62%
“…Furthermore, in silico RNA hybridization revealed a sequence complementary to miR172 in the CeAP2-like cDNA, and the position of this sequence was similar to that in other miR172-targeted AP2 genes from different plants (Figure 3). Since the regulation of the AP2-domain genes by miR172 has been broadly reported in both monocotyledons and dicotyledons (Zhu and Helliwell 2011;Varkonyi-Gasic et al, 2012), our findings indicated CeAP2-like as a putative target gene of miR172 in C. ensifolium. …”
Section: Isolation Of the Ceap2-like Gene In C Ensifoliumsupporting
confidence: 51%
“…miR172 has been the focus of multiple studies using different approaches, such as overexpression, expression of resistant target genes, or mutations in individual loci encoding the miRNA (26)(27)(28)(29)(30)(31)(32)(33)(34)(35). These previous studies suggested that miR172 mainly controls flowering time and floral organ identity.…”
Section: O)mentioning
confidence: 99%
“…Excitingly, a sequence alignment of Pv miR172 and the transcript of PvTPS9 , revealed a possible recognition site in the coding region (Figure S4A). The transcript abundance of the canonical target of miR172, APETALA2 ( PvAP2 ), shows an inverse correlation to that of Pv miR172 during nodulation, an indication that Pv miR172 modulates the expression of PvAP2 in P. vulgaris (Mlotshwa et al, 2006; Glazińska et al, 2009; Wollmann et al, 2010; Grigorova et al, 2011; Zhu and Helliwell, 2011; Varkonyi-Gasic et al, 2012). Here, we found that the PvTPS9 transcript was associated with Pv AGO1-complexes from 14 and 22 dpi nodules along with PvAP2 and Pv miR172, despite the fact that 5′-RACE analysis revealed no evidence of processing for the PvTPS9 transcript (Figure S4C).…”
Section: Discussionmentioning
confidence: 99%